SPECTRUM OF VARIOUS HEMATOLOGICAL DISORDERS INVOLVING BONE MARROW - Shobha Dwivedi; Shailja Maurya; Rajesh Gautam; Amod Kumar Saroj; Nidhi Verma; Pooja; Narendra Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Hematological disorders are the major global public health problems affecting both developing and developed countries with severe consequences for human health as well as socio-economic development. These occur at all stages of the life cycle but are more prevalent in the pregnant women and young children. Objective: To find out spectrum of various hematological disorders involving bone marrow.  Methods: The present study was conducted on fifty patients in department of pathology L.L.R.M Medical College, Meerut referred from outpatient & inpatient Department of Medicine and Pediatrics, SVBP Hospital, attached to L.L.R.M Medical College Meerut. The study was done from March 2018 to June 2019 in patients with symptoms viz., pallor, fever, bleeding manifestations, body aches and pains, hepatosplenomegaly and lymphadenopathy.  Result: Of the 50 cases studied, maximum numbers of cases were of Megaloblastic anemia in 24% followed by20% in Normoblastic anemia, 4% in aplastic anemia and each cases of hemolytic anemia & refractory anemia. In all cases of leukemia 18% cases of chronic leukemia, 16%casesof acute leukemia and observed. In lymphoma, 4% cases Non-Hodgkin's lymphoma & 2% case Hodgkin's lymphoma were observed. In present study one case of each Multiple myeloma, Myelofibrosis, Leishmaniasis, Idiopathic thrombocytopenic Purpura was seen. Bone marrow aspiration and biopsy was done in all the cases. A dry tap on aspiration was obtained in cases of myelofibrosis, aplastic anemia and single case of chronic myeloid leukemia. Bone marrow biopsy was found to be more informative as compared to aspiration in cases of myelofibrosis, aplastic anemia and lymphoma.Conclusion: Bone marrow aspiration as well as biopsy allowed the evaluation of the hematopoietic cellularity. Hypercellular bone marrow was observed in 37 cases.  Hypocellular bone marrow was seen in 2 cases of aplastic anemia and one case of myelofibrosis. In all cases of anemia diagnosis was made by bone marrow aspiration as well as by biopsy